2022
DOI: 10.1111/ene.15304
|View full text |Cite
|
Sign up to set email alerts
|

Is there a correlation between MOG‐associated disorder and SARS‐CoV‐2 infection?

Abstract: Background and purpose Anti‐myelin oligodendrocyte glycoprotein antibodies (MOG‐Abs) distinguish a group of inflammatory disorders which can be preceded by specific or non‐specific infections. A few single cases have been reported in association with SARS‐CoV‐2 infection, but a specific study on the correlation between COVID‐19 and myelin oligodendrocyte glycoprotein (MOG)‐associated disorder (MOGAD) has not yet been performed. The aim of this study was to determine the impact of the pandemic on this condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
1
20
0
2
Order By: Relevance
“…Apart from NMOSD, myelin oligodendrocytes glycoprotein antibody-associated disease (MOGAD) presenting after vaccination have been reported as well ( Francis et al, 2022 ). However, there was no difference in the frequency of serum SARS-CoV-2 IgG in the normal population and newly diagnosed MOGAD patients ( Mariotto et al, 2022 ). The association between infection/vaccination and CNS inflammatory demyelinating diseases is an interesting area for future studies.…”
Section: Subclinical Nmosd Activity?mentioning
confidence: 89%
“…Apart from NMOSD, myelin oligodendrocytes glycoprotein antibody-associated disease (MOGAD) presenting after vaccination have been reported as well ( Francis et al, 2022 ). However, there was no difference in the frequency of serum SARS-CoV-2 IgG in the normal population and newly diagnosed MOGAD patients ( Mariotto et al, 2022 ). The association between infection/vaccination and CNS inflammatory demyelinating diseases is an interesting area for future studies.…”
Section: Subclinical Nmosd Activity?mentioning
confidence: 89%
“…While the global incidence of MOGAD since the beginning of the SARS-CoV-2 pandemic remains unknown, there are reports of increased detection of MOGAD by some neuroimmunological laboratories. ( Mariotto et al, 2022 ) However, to date there has been a relative paucity of reported cases of MOGAD following SARS-CoV-2 infection, suggesting that clinicians have not observed a significant rise in the incidence of MOGAD during this time. Differences in the host response to SARS-CoV-2 may explain why only a small subgroup of individuals develop MOGAD following infection.…”
Section: Discussionmentioning
confidence: 99%
“…8 One study concluded that SARS-CoV-2 may be a trigger of MOGAD as the authors found a higher occurrence of SARS-CoV-2 IgG antibodies in patients with MOGAD, but the difference was non-significant. 9 However, another study showed that only one out of 15 patients tested positive for anti-MOG in a group of post Covid-19 acute disseminated encephalomyelitis (ADEM) or acute hemorrhagic leukoencephalitis. 10 We report four cases with onset of MOGAD after SARS-CoV-2 infection and reviewed previously published case reports with similar associations suggesting a role of SARS-CoV-2 in the pathogenesis of MOGAD.…”
Section: Introductionmentioning
confidence: 99%